Theragnostic 64Cu/67Cu Radioisotopes Production With RFT-30 Cyclotron - Lee, Jun Young; Chae, Jung Ho; Hur, Min Goo; Yang, Seung Dae; Kong, Young Bae; Lee, Jongchul; Ju, Jin Sik; Choi, Pyeong Seok; Park, Jeong Hoon (Frontiers in Medicine, 2022)
64Cu and 67Cu are theragnostic pair radionuclides with promising application in the nuclear medicine. 64Cu is PET nuclide for the non-invasive diagnosis and 67Cu is beta emitter for therapy of various cancers. This study discusses optimization efforts in the production of these radioactive coppers carried out with 30 MeV cyclotron. Optimized conditions include target preparation, chemical separation, and quality control. The production routes of 64Cu and 67Cu were studied based on the nuclear reactions of 64Ni(p,n)64Cu and 70Zn(p,α)67Cu. The produced 64Cu and 67Cu have >99.9% of the radionuclidic purity. The yield at the end of bombardment (EOB) of 64Cu and 67Cu is 28.5 MBq/μAh and 67Cu is 0.58 MBq/μAh, respectively.